IDENTIFICATION OF AREAS AT RISK OF ABRASION APPLICATION OF ELECTRICAL RESISTIVITY TOMOGRAPHY (ERT) METHOD ON NANGAI BEACH, NORTH BENGKULU - Saputra, Bayu; suhendra, Suhendra; Halauddin, Halauddin; lidiawati, Liza; Marcelina, Shyaira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
A study of the underground structures in areas prone to abrasion of Nangai Beach, North Bengkulu Regency. In this study, 2D images of the subsurface structure at the Nangai Beach site were obtained using the Wenner-Schlumberger configuration, while 3D representations were obtained using the electrical resistivity technique (ERT). To protect coastal materials, the main objective of this research is to identify rock types that are resistant to seawater erosion and measure the resistivity of rocks that can be eroded. In addition, software (ERT LAB 64, View Lab 3D and Res2Dinv) was used to analyze the data by processing it and displaying an image of the resistivity value. The interpretation results show that the coastal zone of the study area is dominated by clays with resistivity (>34 Ωm). The shoreline of Nangai beach consists of shale clay (>> 437 Ωm). Rocks having a resistivity value (437 Ωm) are not easily eroded by erosion in shale clay. This is because the rocks known as shale clay have low porosity, resulting in compact rock density. Restoring damaged soil and planting trees near the coast are two ways to slow down the abrasion process. Keywords: Abrasion, Electrical Resistivity tomography (ERT), 2D/3D, Nangai Beach